Comparison of gall bladder bile and endoscopically obtained duodenal bile. Issue 12 (December 1990) - Janowitz, P; Swobodnik, W; Wechsler, J G; Zöller, A; Kuhn, K; Ditschuneit, H
Abstract : In 10 patients with gall stone disease (eight women, two men; mean (SD) age 47.4 (13) years), bile was obtained by endoscopic aspiration after stimulation of the gall bladder with ceruletid and also by fine needle puncture of the gall bladder under local anaesthetic. The total lipid concentration of the puncture bile samples was mean (SD) 11.9 (4.7) g/dl, significantly higher than the endoscopic bile samples (3.9 (3.3) g/dl, p less than 0.001). Total bile acids, phospholipids, and biliary cholesterol (expressed in mol%) and cholesterol saturation index showed no significant differences between the two types of samples. The glycocholic acid concentration in the endoscopically obtained bile (27.7 (6.6) mol% v 23.3 (5.4) mol%; p less than 0.01) was significantly higher than the puncture bile samples. Puncture bile exhibited a significantly shorter nucleation time (3.5 (3.3) days v 19.6 (11.9) days; p less than 0.001). For determination of the nucleation time, endoscopic bile aspiration after gall bladder stimulation with ceruletid led to adequately concentrated samples in 50% of the study subjects. Cholesterol monohydrate crystal formation in native bile was observed in six samples of puncture bile and in three samples of the endoscopically obtained bile. The presence of cholesterol crystals and the determination of nucleation time in the puncture bile were the best discriminants between cholesterol and pigment gall stones and correlated well with computed tomogram analysis.